Pengelompokan Kabupaten/Kota di Provinsi Jawa Tengah Berdasarkan Potensi Pariwisata Tahun 2020 - Sopa Maulidia; Erni Tri Astuti (Politeknik Statistika STIS, 2022)
Tourism is one of the government's strategies to accelerate national economic growth in the 2015-2019 RPJMN because through its multiplier effect the tourism sector can help accelerate national economic growth. Central Java Province in 2020 has an uneven distribution of tourist attractions among other districts/cities. The uneven distribution of the number of tourist attractions is the background for the author in grouping districts/cities in Central Java based on tourism potential. This study uses 8 variables related to tourism potentials. The unit of analysis used in this study were 35 districts/cities in Central Java Province. The analytical method used is k-means cluster analysis which is famous for its ease of algorithm. This study resulted in 4 groups of regencies/cities with low, medium, high, and very high tourism potential, each consisting of 8 regencies/cities, 4 regencies/cities, 22 regencies/cities, and 1 district. The government is expected to know the potential of each region before prioritizing tourism development in Central Java Province.